Anaesthetic Management of a Patient with Fontan Circulation for Laparoscopic Cholecystectomy - Parajuli, Bashu Dev; Suwal, Allen; Sharma Bhattrai, Amit; Ghimire, Basanta; Joshi, Pankaj; Koirala, Megha; Singh Kansakar, Prasan Bir (Journal of Nepal Health Research Council, 2023)
Fontan circulation is a complex surgical procedure carried out in infants in a staged fashion, where caval circulation is connected to the pulmonary circulation, bypassing the heart. The ventricular activity will drive the blood to pulmonary circulation, which, after oxygenation, will return to heart and then will distribute through-out the body. The pulmonary vascular resistance determines the preload, which further depends upon the volume status of the body. This physiology is further complicated by the presence of arrythmia, liver cirrhosis, caval-pulmonary shunt thrombosis and low ventricular activity. Anaesthetic implication of such case includes challenges to manage preload, maintenance of pulmonary vascular resistance, preservation of the single ventricular function and avoidance of circuit thrombosis. Here we present a case of 15 years female who presented to our centre for laparoscopic cholecystectomy.Keywords: Cholecystectomy; Circulation; Laparoscopic.